The Position of the Indonesian Language in the SPK School Language Policy Document: A Case Study of International Curriculum Schools - Nugraha, Edy; Prima Gusti Yanti; Wini Tarmini (Jurnal Sastra Indonesia, 2024)
The Indonesian policy can make Indonesia the official language. Although Indonesian comes from Pasar Malay, through the Youth Pledge process, it can change its status to Indonesian. The implication of Indonesian as an official language is that it is used in education as the language of instruction. However, in Indonesia, there are types of schools with an international curriculum that use English. This study discusses the position of Indonesians in the global curriculum school language policy document. The research method uses content analysis that focuses on the position of the Indonesian language. This research uses Spolsky's language policy theory in the form of ideology, practice, and language management. The study results reveal that Indonesians still have an essential position in the language policy.  Although English is the lingua franca, the primary language of instruction, and the medium of instruction, Sampoerna Academy still positions Indonesian as an essential language to be used and taught. This is in line with their ideology of upholding multiculturalism, multilingualism, and respect for the mother tongue. All the ideologies and philosophies of the language presented are also applied in language settings and practices.